2017
DOI: 10.1186/s12882-016-0428-y
|View full text |Cite
|
Sign up to set email alerts
|

Dengue fever in renal transplant patients: a systematic review of literature

Abstract: BackgroundDengue fever in renal transplanted patients has not been studied well, and we review all the literature about episodes dengue fever in renal transplant patients.MethodsThe aim was to describe clinico-pathological characteristics, immunosuppressive protocols, need renal outcome and mortality. PubMed, LILACS, Google Scholar and Research Gate were searched for “Dengue” and “Renal/Kidney Transplantation” with no date limits. Hits were analyzed by two researchers separately.ResultsFever, myalgia, arthralg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
4
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 10 publications
6
46
4
2
Order By: Relevance
“…The only available systematic review by Weerakody et al includes 10 records (inclusive of case reports) of dengue in transplant recipients . Of the 29 patients with clinical outcomes, fever, myalgia, and headache were common manifestations seen in over 90% of the patients; arthralgia was rare (25%); thrombocytopenia was common (88%); and transient graft dysfunction (38%) was similar to our case series.…”
Section: Discussionsupporting
confidence: 74%
“…The only available systematic review by Weerakody et al includes 10 records (inclusive of case reports) of dengue in transplant recipients . Of the 29 patients with clinical outcomes, fever, myalgia, and headache were common manifestations seen in over 90% of the patients; arthralgia was rare (25%); thrombocytopenia was common (88%); and transient graft dysfunction (38%) was similar to our case series.…”
Section: Discussionsupporting
confidence: 74%
“…According to published data, CHIKV in solid organ transplant recipients seems to have a benign course and favorable outcome (19,20), whereas data for DENV in these patients are less clear. Case descriptions report uncomplicated outcomes, whereas a recent literature review reported a significantly higher incidence of severe dengue and a higher mortality rate among transplant patients with dengue (21)(22)(23). A recent report of DENV, ZIKV, and CHIKV infections diagnosed in hematopoietic stem cell transplant recipients and oncohematologic patients found prolonged viremia in those with DENV and viruria in those with ZIKV; the most common complication was thrombocytopenia, but all patients survived without sequelae (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed a lower frequency of classic symptoms and a higher incidence of severe disease and mortality among dengue‐infected solid organ transplant recipients, without infection‐related graft rejection . Little is known about the natural history of Zika virus infection in organ recipients, with some fatal cases reported .…”
Section: Discussionmentioning
confidence: 99%